2014
DOI: 10.1371/journal.pone.0089413
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Multiplex Genetic Engineering in Rats Using CRISPR/Cas9

Abstract: The CRISPR/Cas9 system has been proven to be an efficient gene-editing tool for genome modification of cells and organisms. Multiplex genetic engineering in rat holds a bright future for the study of complex disease. Here, we show that this system enables the simultaneous disruption of four genes (ApoE, B2m, Prf1, and Prkdc) in rats in one-step, by co-injection of Cas9 mRNA and sgRNAs into fertilized eggs. We further observed the gene modifications are germline transmittable, and confirmed the off-target mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 24 publications
1
77
0
Order By: Relevance
“…Furthermore, rapid gene disruption in mouse, rat and rabbit embryo by microinjection of TALENs has also been reported [16][17][18]. TALENs have been successfully used to correct β-thalassemia patients using a non-viral approach via efficient generation of iPSCs from the patient cells [1] demonstrating that this strategy could be used for correction of mutation. , TALEN domain and Cas9·sgRNA-induced DSBs can be repaired by either NHEJ or by HDR pathways.…”
Section: Earlier Approaches For Gene Correctionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, rapid gene disruption in mouse, rat and rabbit embryo by microinjection of TALENs has also been reported [16][17][18]. TALENs have been successfully used to correct β-thalassemia patients using a non-viral approach via efficient generation of iPSCs from the patient cells [1] demonstrating that this strategy could be used for correction of mutation. , TALEN domain and Cas9·sgRNA-induced DSBs can be repaired by either NHEJ or by HDR pathways.…”
Section: Earlier Approaches For Gene Correctionmentioning
confidence: 98%
“…Derivation of patient-specific induced pluripotent stem cells (iPSCs) from somatic cells and the subsequent correction of the disease-causing mutations represent a possible strategy to achieve this goal. Corrected iPSCs can undergo indefinite self-renewal without losing the ability to differentiate into all cell types and may useful for autologous transplantation [1]. However, this strategy has own limitations for the clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Rat eyes are larger and therefore easier to inject and rats can be easier to handle in the context of obtaining awake IOP readings. The rat is increasingly being used for mechanistic studies of glaucoma pathophysiolgy, supported by the increasing availability of genetically altered rats (Ma et al, 2014). Gene array analyses in wild type strains have been valuable in pinpointing potential mechanism for early axonal damage (Johnson et al, 2011;Agudo et al, 2008).…”
Section: Ratmentioning
confidence: 99%
“…Several studies have shown that the CRISPR/Cas9 system is an effi cient tool for generating targeted KO rats (Li et al 2013a , b ;Ma et al 2014a , b ). We have also generated a targeted KO rat for the coat color gene, tyrosinase ( Tyr ), by microinjecting target-specifi c gRNA and Cas9 mRNA into fertilized eggs (Yoshimi et al 2014 ).…”
Section: Knockout Rats With Crispr/cas9mentioning
confidence: 99%
“…This system can also introduce multiple gene mutations in one step by microinjecting Cas9 mRNA and multiple gRNAs into rat zygotes. This is one of the signifi cant advantages of this system (Cong et al 2013 ;Wang et al 2013 ;Ma et al 2014a ). Although it is possible to generate rats with multiple mutations by breeding together rats with single mutations, the process is costly and time-consuming.…”
Section: Knockout Rats With Crispr/cas9mentioning
confidence: 99%